Effects of ATF2/TSC1 on epilepsy by modulating the microphages polarization of microglia - Wenjiao Huang; Wenli Chen; Zhong Zhao; Lingchun Liu; Yuanyuan Zhao; Xinzhang Chen; Rong Li (Scientific Reports)
Abstract Epilepsy (EP) is a chronic nervous system disease characterized by recurrent attacks, and its causes are complicated. Inflammatory reaction mediated by microglia is an important factor in the progression of EP. Activating transcription factor 2 (ATF2) can be used as a transcription factor to regulate the microglia-mediated inflammatory response, but its role in EP is unclear. In this study, kainic acid (KA) was used to induce the EP cell and mouse model. Real-time polymerase chain reaction was used to detect ATF2, TNF-α, IL-6, TGF-β, and IL-10 mRNA expression. ATF2, INOS, ARG1, and TSC1 protein levels was examined by western blot. The fluorescence intensity of ATF2, IBA1, CD80, and CD206 was examined by immunofluorescence staining. The cell ratios of CD80, IL-1β, CD206, and CD63 were detected by flow cytometry. Dual-luciferase reporter and chromatin immunoprecipitation assays were conducted to verify the interaction between ATF2 and TSC1. Hematoxylin & eosin and Nissl staining were used to observe the structure of hippocampus and Nissl bodies. The results indicated that KA induced M1 polarization of HMC3 cells and increased the levels of TNF-α and IL-6 mRNA by activating KA receptors, and inhibiting KA receptors attenuated the M1 polarization of KA-induced HMC3 cells. ATF2 expression was increased in KA-induced HMC3 cells and hippocampal tissues of mouse, while TSC1 expression was repressed. ATF2 knockdown diminished the M1 polarization of KA-induced HMC3 cells, enhanced the M2 polarization, and relieved neuroinflammation in EP mouse. TSC1 overexpression inhibited M1 polarization in KA-induced HMC3 cells. Dual luciferase and chromatin immunoprecipitation results revealed that ATF2 bound to the promoter of TSC1 and negatively regulated the transcription of TSC1. In conclusion, inhibition of ATF2 and promotion of TSC1 transcription may be a new pathophysiological mechanism for the treatment of EP neuroinflammation.